ANALISIS DAN EVALUASI JABATAN BERBASIS KOMPETENSI: STUDI KASUS SEKRETARIAT DAERAH PROVINSI JAWA BARAT - Frili Asia Musfrida; Stella Valencia Kurniawan; Derivan Herdiansyah; Erwin Rio Dafa Ramadhan; Gurawan Dayona Ismail (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze and evaluate competency-based job positioning within the General Bureau of the Regional Secretariat of West Java Province, with a specific focus on the divisions of General Affairs, Financial and Asset Administration, and Household Affairs. Based on simulated data, it is indicated that 73% of employees have not undergone comprehensive competency mapping, while 42% of positions exhibit workload mismatches. Employing a qualitative case study approach, this research refers to the regulatory frameworks of Permenpan-RB No. 1 of 2020 and No. 38 of 2017. Data collection techniques include in-depth interviews, document analysis, observation, and focus group discussions (FGD), with data analysis carried out using the Miles and Huberman (2014) interactive model. The findings of this study are expected to offer strategic recommendations for competency mapping of the State Civil Apparatus (ASN), the enhancement of the merit system, and the development of competency-based human resource policies within the General Bureau of the Regional Secretariat of West Java Province.